D Podcast Video dan Strategi Pemilihan Konten dalam Times Indonesia Podcast pada Times TV Jogja - Karunianingsih, Diyah Ayu (Jurnal Pekommas, 2023)
Podcast users continue to increase, including the development of video podcasts. The phenomenon of online media that presents video podcast continues to grow. Even online media can publish content not only on podcast applications such as Spotify, Anchor and other applications, but also uploaded on YouTube channel. Times Indonesia Podcast is one of those that creates video podcast content which is then uploaded to the youtube channel. The research was conducted on the Yogyakarta Regional Times Indonesia Podcast video podcast. This study aims to find a video podcast model and content selection strategy as an alternative broadcasting medium for the Times Indonesia Podcast broadcast program on Times TV Jogja. The research was conducted using a qualitative descriptive method with phenomenological research methods. Data collection techniques in the form of interviews and observations. The results of the study found that the video podcast model developed or produced by Times Indonesia Regional Yogyakarta is a type of interview podcast and the publication model does not use the podcast platform but is published using the youtube channel. The topic selection strategy refers to topics that are currently being discussed by the public, viral topics, and national topics related to regional issues in Yogyakarta.